Knowledge and Attitudes Concerning Antibiotic Use and Resistance among the Public in Pulau Pinang, Malaysia - Halim, Nur Ashila Azleen Ab (Malays J Med Sci, 2018)
The aim of this cross-sectional study was to evaluate the knowledge and attitudes concerning antibiotic use and resistance among members of the local community in Pulau Pinang, Malaysia. The study was conducted among 326 residents of the Jelutong district, Pulau Pinang state, from August to October 2013. A self-administered five-part questionnaire was used for the data collection. The respondents exhibited inadequate knowledge of antibiotics in general. Approximately 80% of them did not know the indications for antibiotic use, while 76% believed that antibiotics were useful in terms of resolving viral fever. Additionally, 52.6% believed that antibiotics could be used to treat all types of infections. Inadequate knowledge of antibiotic resistance was also evident among the respondents, since 72.9% of them did not agree that resistant bacteria can spread from human or animal to human, while 32% were unaware that bacteria can develop resistance to antibiotics. More than 60% of respondents admitted that they took antibiotics in order to accelerate their recovery from illness, while 34.8% claimed that they only stopped taking antibiotics when they felt better. The findings hence indicate that most respondents had poor knowledge and attitudes concerning antibiotic use and resistance, which suggests the need for more community-based educational campaigns designed to improve the public’s knowledge and attitudes regarding antibiotics.